Envolvimento de p38 MAPK no ciclo de vida do Vaccinia virus - Jonas Dutra Albarnaz (2014)
Viruses rely extensively on host cell functions to complete their lifecycles. During infection, viruses co-opt signaling pathways, key regulators of cell physiology, to achieve an intracellular milieu suitable for productive viral reproduction and spread. The functional relevance of host MAPKs (mitogen-activated protein kinases) ERK1/2 and JNK1/2 for multiplication and dissemination, respectively, of Vaccinia virus (VACV) is well known, but the involvement of p38 MAPK is underappreciated. Therefore, this study evaluated the activation and functional relevance of p38 MAPK in the lifecycle of VACV Western Reserve (WR), a laboratory strain, and VACV Belo Horizonte (VBH), a strain isolated from a mousepox outbreak in an animal facility. The pharmacological inhibitor of p38α/β MAPK SB203580 inhibited differentially the multiplication of VACV-WR and VBH in mouse A31 cells, human HeLa cells and non-human primate BSC-40 cells. Inhibition of viral replication was associated with a reduced accumulation of some late viral proteins and, in VBH-infected A31 cells, a diminished formation of mature virions (MVs). Activation p38 MAPK was detected late during infection, as well as the phosphorylation of its substrate MK2 by a signal triggered prior to viral genome replication. Reduction in VACV-WR dissemination was observed in the presence of SB203580 in the cell lines tested. The effects of SB203580 on VACV multiplication and dissemination occurred in a p38α MAPK-independent manner. Taken together, these results demonstrate that p38 MAPK is co-opted by VACV and plays pleiotropic functions during infection, supporting production and spread of the viral progeny.